Determination of Eating Attitude and Mindful Eating Scores of Patients in Turkey - Cebirbay, M. Ali; Kitis, Cağrı (Progress in Nutrition, 2022)
The study aims to evaluate the status of eating attitude and mindful eating of adult patients (n=905) who applied to diet polyclinics in hospitals in Afyonkarahisar, Turkey. The data were collected by face-to-face interviews using a 4-part questionnaire form, including socio-demographic features and nutritional habits, anthropometric measurements, Eating Attitude Test (EAT-40) and Mindful Eating Questionnaire (MEQ-30). Data were analyzed using SPSS 25.0 version. In total, 5.4% of patients had eating disorders; underweight patients were associated significantly with an overall eating disorder (p<0.05), females’ EAT-40 scores were higher than males (p<0.001). Diet application before coming to the clinic, diet type, home delivery fast food consumption and night eating were significantly different associated with an eating disorder (p<0.05). The MEQ-30 total score (x̄±SE) of the patients was 2.82±0.45 (p<0.05) and emotional eating, eating control, awareness, disinhibition and interference differed significantly (p<0.05). Underweight patients’ in both EAT-40 and MEQ-30 total scores differed (p<0.05) in other BMI groups. Disinhibition, emotional eating and eating control had a significant impact (p<0.05) on sub-scales of MEQ-30. EAT-40 total scores were not correlated, but MEQ-30 total scores had a weak correlation (r=0.106; p<0.000) by BMI and a positive correlation between total MEQ-30 and all subscale scores (p<0.000). The findings suggest that differences between eating disorder predisposition and mindful eating sub-scales differed in BMI and eating attitude and of patients’ awareness should be increased and patients can be informed about this issue through further nutrition counseling.